2006
DOI: 10.1246/cl.2006.1374
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Fabrication to Cellulose-based Nanoparticles with Thermo-responsivity and Carboxyl Functional Groups

Abstract: Cellulose-based nanoparticles having thermo-sensitivity and carboxyl functional groups were fabricated for the first time without using any surfactant and organic solvent. The nanoparticles exhibit rapid and reversible dispersion–aggregation changes in response to narrow range temperature alternation near our body temperature as demonstrated by dynamic light scattering, which may be utilized in biomedical fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The synthesis of microgels follows our previous report, which is based on the graft polymerization of AA from HPC at the presence of the bifunctional monomer MBA where the polymerization was initiated by CAN. An aqueous solution of 37 mg CAN in 1.25 mL of 0.1 mol/L nitric acid and 0.4 mL AA were successively added to 50 mL of 1.2 wt % aqueous solution of HPC under gentle stirring and nitrogen bubbling.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of microgels follows our previous report, which is based on the graft polymerization of AA from HPC at the presence of the bifunctional monomer MBA where the polymerization was initiated by CAN. An aqueous solution of 37 mg CAN in 1.25 mL of 0.1 mol/L nitric acid and 0.4 mL AA were successively added to 50 mL of 1.2 wt % aqueous solution of HPC under gentle stirring and nitrogen bubbling.…”
Section: Methodsmentioning
confidence: 99%
“…Moving away from dextran, thermoresponsive nanoparticles based on a temperature‐sensitive polysaccharide, hydroxypropyl cellulose (HPC), were fabricated via the GISA approach using AA as the monomer . HPC is a derivative of cellulose (Fig.…”
Section: Synthetic Strategies For Polysaccharide‐based Nanocarriersmentioning
confidence: 99%
“…19 25 Such anomalous behavior was also reported by Dou et al who observed an increase in the size but only at temperatures around and higher than the LCST (41 C). 26 At temperatures greater than the LCST the hydrophilicity to hydrophobicity transition of HPC chains in water may induce self-association, leading to the formation of metastable nanoparticle aggregates. 19 25 26 Gao et al also reported that HPC chains may form different metastable aggregates depending on how the system is brought to that temperature.…”
Section: Tgamentioning
confidence: 99%